Synthesis of Cu- and Ag-modified flower-like Ni(OH)₂ nanocomposites - Vu , Hung Sinh; Nguyen , Thi Cam Dieu; Nguyen , Duong Thien; Huynh , Thi Tuy Ngoc; Nguyen, Dang Giang Chau; Nguyen, Duc Cuong (Hue University Journal of Science: Natural Science, 2025)
In this report, a simple template-free hydrothermal method was used to synthesise flower-like Ni(OH)2 structures modified with Ag and Cu. The Ni(OH)2 microflowers were formed via the self-assembly of ultrathin nanosheets with a thickness of approximately 2–3 nm. The incorporation of Ag and Cu at appropriate concentrations preserved the three-dimensional flower-like architecture of Ni(OH)2. For the Ag-Ni(OH)2 composite, Ag nanoparticles were uniformly dispersed on the Ni(OH)2 nanosheets. In contrast, no Cu(OH)2 phase was detected in the Cu-Ni(OH)2 composite, likely because of Cu substituting the Ni sites within the Ni(OH)2 lattice. Owing to their unique three-dimensional (3D) flower-like structure, large specific surface area, and enhanced physicochemical properties introduced by metal modification, these materials are potentially suitable for applications in electrochemical sensing, catalysis, and biomedical fields.